Needs Assessment for Teacher Professional Development in General Buddhist Schools Area 7 - Vatasatdho, Phrapalad Honda; Kittimatee, PhramahaKitti (Journal of Buddhist Education and Research (JBER), 2024)
This research aimed to study the current state, desired state, and needs assessment for teacher professional development in General Buddhist Schools Area 7. The sample consisted of 218 administrators and teachers from General Buddhist Schools Area 7, selected from a population of 506 using Krejcie & Morgan’s (1970) table. The research instrument was a validated questionnaire with acceptable reliability. Data were analyzed using mean, standard deviation, and modified Priority Needs Index (PNImodified). The findings revealed that the needs for teacher professional development in General Buddhist Schools, ranked from highest to lowest, were: 1) collaborative networks of forces (PNImodified = 0.51), 2) individual teacher needs (PNImodified = 0.35), 3) student and teacher learning (PNImodified = 0.31), 4) supportive structures and environment (PNImodified = 0.28), and 5) acting under professional standards (PNImodified = 0.26). The results indicate that teachers in Buddhist schools have the highest need for professional development through collaborative work processes and the establishment of professional learning communities, which aligns with the specific context of schools that have diverse personnel and limited resources.